Assessment of patulin in different cultivars of apples, juices, and distribution in decay portion - Iqbal, Shahzad Zafar; Akbar, Mehnaz; Abdull Razis, Ahmad Faizal; Waqas, Muhammad (Taylor & Francis, 2022)
Patulin (PAT) is a toxic class of mycotoxins, which is produced by fungi mainly by Penicillium expansum. Samples of apples (740 samples from Amri, Gacha, Kala Kulu, and Golden cultivars) and of apple juices (740 samples) available domestically in Pakistan were analysed for PAT contamination using HPLC with a UV detector. The results have shown that 67.5% and 61.6% samples of apples and juices were found to be positive with PAT, respectively. The highest averages levels 310.8 ± 21.5 μg/kg and 290.8 ± 14.6 μg/kg were found in samples of golden apples and juices, respectively. The findings have shown that 44.8% samples of apples were found levels higher than the European Union (EU) permissible limit (i.e. 50 µg/kg). Furthermore, 41.0% samples of apple juices have amount of PAT higher than the recommended limit of EU. The artificially inoculated apple with Penicillium expansum, a level 5080 ± 230.4 μg/kg was found in the decayed section. The maximum dietary intake of PAT was estimated to be 15.7 and 17.93 µg/kg bw/day in males and female individuals. The results have shown that even removing the decayed portion of apples, a considerable amount of PAT penetrates during the process of making juices.